Clinical Practice Guidelines for Severe Sepsis Treatment. - Julio Héctor Jova Dueñas; Diosdania Alfonso Falcón; Marcos Diosdado Iraola Ferrer; Inti Santana Carballosa; José Noel Marrero. (Medisur, 2009)
Clinical Practice Guidelines for Severe Sepsis Treatment. It is a syndrome of inflammatory systemic response caused by documented infection (clinical and/or microbiological), associated with organic dysfunction (respiratory, renal, hepatic, cardiovascular, haematological and neurological), hypotension or hypoperfusion. This document includes a review and update of the concept, risk factors, diagnosis and treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.